Should patients be informed about the side effects of psychotropic drugs? According to us: Yes - Atmaca, Murad; Korucu, Tuba; Cekic, Sevier; Kazgan, Ash; Keles, Denizhan Danaci; Tabara, M. Fatih; Korkmaz, Sevda (Elsevier Ireland Ltd, 2018)
Background: In our daily clinical practice, we observe that patients who were informed about the probable side effects of any medication experience less side effects. For this reason, we decided to examine this in a systematic investigation. Methods: We divided patients into two groups, the informed and uninformed one about side effects of the drugs. During the control examination, tolerability of the drugs given was questioned in detail. Results: At the end of one month, the mean total UKU score was statistically significantly lower in patients from the informed group compared to that of the uninformed one (p < 0.05). The proportion of patients who discontinued the drug during the one month-period was statistically significantly higher in the uninformed group compared to informed group 9% in the informed group vs. 25% in the uninformed group) (p < 0.05). Conclusions: Finally, we found that giving information about the side effects of a psychopharmacological agent seems to be useful and to provide beneficial effects on the tolerability of the drug, independent of the kind of psychotropic agent.
Keywords: Psychotropic drugs; Informed; Side effects; Nocebo